Mosul Brigade in the era of the British Mandate - Studying the Prophet of Political History - (1932-1920) AD (Journal of the College of Basic Education, 2022)
The data contained between the two covers of this research show that Mosul has undergone many developments over the agessuccessive historical events and reflected on its internal conditions.In the era of ancient history, Mosul was part of the Assyrian Empire, and in the era of historyAl Waseet was part of the Islamic Caliphate State, and in the era of modern history it was part of the last CaliphateIslamic (Ottoman Sultanate), and in the era of contemporary history and after the collapse of the last Islamic caliphate was exposedThe Ottoman Islamic state of Mosul for a new Crusader invasion.